2016
DOI: 10.3390/rs8010039
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Thermal Imagery to Detect the Seasonal Evolution of Crop Water Status in Peach, Nectarine and Saturn Peach Orchards

Abstract: In the current scenario of worldwide limited water supplies, conserving water is a major concern in agricultural areas. Characterizing within-orchard spatial heterogeneity in water requirements would assist in improving irrigation water use efficiency and conserve water. The crop water stress index (CWSI) has been successfully used as a crop water status indicator in several fruit tree species. In this study, the CWSI was developed in three Prunus persica L. cultivars at different phenological stages of the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 35 publications
1
57
0
3
Order By: Relevance
“…Some authors proposed that phenological stages could have affected the CWSI accuracy of water stress prediction. Möller et al [26] found that in vineyards at the end of the growing season, leaves were in a senescence condition and may not have been representative of complete canopy conditions, and Bellvert et al [39] found differences between varieties and the phenological stage in vineyards, as well as peach and nectarine orchards [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors proposed that phenological stages could have affected the CWSI accuracy of water stress prediction. Möller et al [26] found that in vineyards at the end of the growing season, leaves were in a senescence condition and may not have been representative of complete canopy conditions, and Bellvert et al [39] found differences between varieties and the phenological stage in vineyards, as well as peach and nectarine orchards [41].…”
Section: Discussionmentioning
confidence: 99%
“…Still, the method has been mostly used for research purposes only. Recently, however, the development of both cheaper image acquisition systems and user-friendly, powerful data image processing packages has substantially increased the potential of the method for irrigation scheduling in commercial orchards [55,56]. Thermal readings can be made both at the plant level (ground-based imagery) [55,57] and from above the crop (airborne imagery), after installing the sensors on towers or cranes [58,59], on unmanned aerial vehicles (UAVs), also known as remote piloted aerial systems (RPAS) [60], planes [61] or satellites [62,63].…”
Section: Thermal Sensingmentioning
confidence: 99%
“…Ground-based and airborne thermal images can be combined to assess within-orchard spatial heterogeneity in water status, as demonstrated with grape [64] and olive plants [65]. The principles of thermal sensing are described elsewhere [66,67] and nice examples on both the linking between thermal imaging to main physiological indicators [68] and the use of thermal imaging for irrigation scheduling [56,60,66,69] can be found in the literature.…”
Section: Thermal Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bellvert et al [172] measured the CWSI in three peach cultivars (Prunus persica L.) throughout different growing seasons. They measured the canopy temperature of well-watered trees using high-resolution thermal imagery obtained from an airborne platform and related it to leaf water potential (ψ L ) as a water stress indicator.…”
Section: Si Cwsi = (T Leaf − T Wet )/(T Dry − T Wet )mentioning
confidence: 99%